Indirect interactions among tropical tree species through shared rodent seed predators: a novel mechanism of tree species coexistence. (4th May 2015) - Garzon‐Lopez, Carol X.; Ballesteros‐Mejia, Liliana; Ordoñez, Alejandro; Bohlman, Stephanie A.; Olff, Han; Jansen, Patrick A.; Rejmanek, Marcel
Abstract The coexistence of numerous tree species in tropical forests is commonly explained by negative dependence of recruitment on the conspecific seed and tree density due to specialist natural enemies that attack seeds and seedlings ('Janzen–Connell' effects). Less known is whether guilds of shared seed predators can induce a negative dependence of recruitment on the density of different species of the same plant functional group. We studied 54 plots in tropical forest on Barro Colorado Island, Panama, with contrasting mature tree densities of three coexisting large seeded tree species with shared seed predators. Levels of seed predation were far better explained by incorporating seed densities of all three focal species than by conspecific seed density alone. Both positive and negative density dependencies were observed for different species combinations. Thus, indirect interactions via shared seed predators can either promote or reduce the coexistence of different plant functional groups in tropical forest.